A toggle switch of visual awareness?. (March 2015) - Le, Ada; Stojanoski, Bobby B.; Khan, Saniah; Keough, Matthew; Niemeier, Matthias
Abstract: Major clues to the human brain mechanisms of spatial attention and visual awareness have come from the syndrome of neglect, where patients ignore one half of space. A longstanding puzzle, though, is that neglect almost always comes from right-hemisphere damage, which suggests that the two sides of the brain play distinct roles. But tests of attention in healthy people have revealed only slight differences between the hemispheres. Here we show that major differences emerge if we look at the timing of brain activity in a task optimized to identify attentional functions. Using EEG to map cortical activity on a millisecond timescale, we found transient (20–30 ms) periods of interhemispheric competition, followed by short phases of marked right-sided activity in the ventral attentional network. Our data are the first to show interhemispheric interactions that, much like a toggle switch, quickly allocate neural resources to one or the other hemisphere.